Satellite-based Monitoring of Vegetation Cover of Lalbagh Botanical Garden, Bengaluru, Karnataka, India - Malini A. Shetty; Parinitha Mahishi; Priyadarshini Pillai; R.K. Somashekar (Geography, Earth Science and Environment: Research Highlights Vol. 9, 2025)
Lalbagh Botanical Garden is Bengaluru’s oldest garden, spread across 240 acres, and is home to a wide array of plants from around the world, a treasure house of biological diversity. Lalbagh has 2,950 spp. of plants and trees. It was started in 1760, was given the status of a Government Botanical Garden in 1856, and since then it has been an internationally renowned center for scientific study of plants and botanical artwork, and also conservation of plants. Lalbagh Botanical Garden, with a high diversity of species, provides a storehouse of genetic resources within the region, and it also provides food and pharmacological resources for a range of species such as birds, mammals, reptiles, and insects. The aim of the study is to give an overall picture of vegetation distribution and canopy coverage in different parts of Lal Bagh through satellite imagery. In the present study, Quick Bird imagery of 2005 is used for comparative assessment of NDVI and TNDVI indices with supervised classified imagery of Lalbagh Botanical Garden, one of the largest and oldest botanical gardens in Bengaluru. The NDVI and TNDVI transformed imagery of Lalbagh showed variation in their values. The different land use classes of supervised classified imagery showed more resemblances to the NDVI than TNDVI. It was observed that 33% of Lalbagh’s 240 acres is covered with a thick canopy comprising mainly large mature trees. Small-statured ornamental specimens and many small trees growing in thickets like groupings constitute a thin canopy, covering 20% area. Water constitutes about 13%. The rocky area is present on the North West, comprising about 12%, and the Grass area about 16.6%. The study concluded that in order to achieve environmental sustainability, the city should increase both its percentage of green open space and m2 of urban green open space per capita. More and more efforts should be made in this regard to increase the green spaces in the city by maintaining the old green spaces like botanical gardens, parks, and avenue trees. There is a need to have a clear account of existing green spaces. This study gives various land uses of the entire Lalbagh in a broader picture and a more supplementary study is needed to give tree-wise distribution in the entire Lalbagh.